Exploring the Impact of Achievement vs. Study Skills on College Students’ Perceived Academic Stress: A Comparative Analysis - Tesfahun, Abera (The Indonesian Institute of Science and Technology Research, 2025)
Research has demonstrated that study skills can enhance academic performance; however, the understanding of how varying levels of study skills and academic achievement affect academic stress is limited. This study aimed to investigate the effects of college students' study skill levels and academic achievement on their academic stress. A total of 351 randomly selected college students from 16 different fields of study participated. Data were collected via a questionnaire that assessed academic stress related to students’ workloads, self-perceptions, academic expectations, study skills and academic achievement (measured by the CGPA). The analysis revealed that both study skill level and academic achievement have a statistically significant main effect on academic stress, with different levels of study skills and achievement being associated with varying levels of academic stress and a modest effect size. However, the interaction effect between study skill level and academic achievement in relation to perceived academic stress was not statistically significant. Post hoc tests indicated that students with low academic skills reported lower academic stress than did those with average academic skills did, and students with low academic achievement experienced greater academic stress than did their high-achieving counterparts did. The findings suggest important implications for educators, counselors and college students, emphasizing the need for targeted interventions to address study skills and achievement-related stress.